1999
DOI: 10.1021/la980490x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis and Characterization of Gold and Other Noble Metal Nanodispersions in Sol−Gel-Derived Organically Modified Silicates

Abstract: A general approach to prepare nanodispersions of noble metals in organically modified silicates is presented with particular emphasis on the synthesis of gold nanodispersion and its characterization. Organically modified sol−gel monomers containing amine functional groups are used to stabilize the metal salts before the reduction step and to cap and prevent coagulation of the metal sol after reduction and through gel formation, drying, and aging. Uniform spherical metal nanodispersions of Au, Pt, and Pd with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 47 publications
(59 reference statements)
11
121
0
Order By: Relevance
“…Further increasing its concentration, 4,4'-dipyridine began to suppress two ECL signal at the same time, as shown in Figure 5. As reported [33,34], there exit strong affinity between Au À N bond. Concentrated 4,4'-dipyridine can formed a dense monolayer on gold electrode surface which otherwise exclude electron transfer.…”
Section: Pyridine Effect On Gold Electrodesupporting
confidence: 63%
See 1 more Smart Citation
“…Further increasing its concentration, 4,4'-dipyridine began to suppress two ECL signal at the same time, as shown in Figure 5. As reported [33,34], there exit strong affinity between Au À N bond. Concentrated 4,4'-dipyridine can formed a dense monolayer on gold electrode surface which otherwise exclude electron transfer.…”
Section: Pyridine Effect On Gold Electrodesupporting
confidence: 63%
“…Previous reports [33,34] showed that there exists strong affinity between gold and nitrogen bond, as well as platinum and nitrogen bond. So it is reasonable to presume that pyridine which contains nitrogen atom in the molecule could adsorb at noble metal electrode surface as surfactant [25 -30].…”
Section: Introductionmentioning
confidence: 96%
“…APS-Au NPs were synthesized by a simple chemical reduction strategy (Bharathi et al 1999). In typical, total of 10 mL of sol with molar ratios of 100:0.1, 100:1, and 100:10 (3-(aminopropyl)triethoxysilane (APS)/HAuCl 4 ) were prepared by dissolving appropriate amount of APS and Au salt in methanol and 1 mL of 0.01, 0.1, and 1.0 M HAuCl 4 .…”
Section: Fabrication Of Sensor Platformmentioning
confidence: 99%
“…Unlike most gold colloid, few amount of nonspherical particles beside most spherical one was observed. These non-spherical particles seemed to be fabricated by gathered interference of two or three spherical particles during the nucleation process [14,23]. Spectrophotometry is another important aspect for characterization of gold nanoparticles.…”
Section: Characterization Of the Cmcs-aunps Nanocomposite:-mentioning
confidence: 99%